Experience in the Implementation of Project Activities at the University: by the Example of the Analysis of Models of Professionalism in the Research and Historical Retrospective - Androushenko, Oxana Vladimirovna; Khechieva, Aleksandra Tserenovna; Brasheva, Albina Aleksandrovna; Katkova, Ekaterina Aleksandrovna (Razvitie obrazovaniâ (Online), 2022)
The article presents the results of students' project-research activities carried out within the work of the scientific circle and project gas pedal of the Department of Human Resources Management at Volga Region Institute of Management named after P. A. Stolypin – branch of Russian Academy of National Economy and Public Administration. P.A. Stolypin Volga Institute of Management – branch of Russian Academy of National Economy and Public Administration. The aim of the article is to study and analyze the models of professionalism of managerial activity of famous Russian and Soviet statesmen in the research-historical retrospective. The material of the manuscript is an experimental approbation of the method of reconstruction of the psychological profile of famous historical figures. In particular, the famous Soviet aircraft designer S.P. Korolev. The methods of research include the analysis and synthesis of biographical and autobiographical material, questioning of experts with the help of standardized interviewing techniques. Also, the article considers in detail the stages of professional development according to E.A. Klimov, including 8 phases. R.M. Belbin's «Group Roles» test identified the dominant roles in team interaction. By the method of Fetiskin, V.V. Kozlov, G.M. Manuilov styles of professional-activity communication were revealed, psychodynamics was measured by A. Bass and A. Darkey questionnaire. Conclusions on the set of competencies and psychological characteristics that ensure the successful implementation of professional activity are presented as the results of the study. In particular, the thesis about the uniqueness of the biographical contour that forms an individual managerial style is expressed.